Fracassos na aquisição: questões para a clínica de linguagem - Oliveira, Mariana Trenche de (2024)
Many children who don't speak, read or write, or who speak and/or read automatically and without meaning to others, arrive at the speech therapy clinic with a medical diagnosis of Autism Spectrum Disorder or a psychoanalytic diagnosis of childhood Autism. However, they resist usual clinical decisions, raising to questions about the diagnosis, direction of treatment and its effects, which creates demands for theorization about speech, the subject and the clinic. In this qualitative research, we sought to delimit and discuss a set of essential questions, derived from clinical practice, in order to enunciate the specific nature of the Language Clinic with these children. The clinical case narratives were constructed based on notes, recordings, transcriptions, reports and case discussion records and session segments were analyzed in the light of European structuralism. The referral of these children to language clinicians was problematic. Despite receiving the same demand as speech therapists, they do not recklessly adhere to diagnostic classifications. Language clinicians do not look for traces of a pathology, but traces of a speaker's unique relationship with language. Regarding the differential diagnosis between these children and those with Language Delay, a diagnosis was proposed that took into account the presence or absence/fragility of the establishment of so-called structuring games - dialogical, precursors of the possibility of the child, who still does not speak, engaging in dialogue with the body and voice (LIER-DEVITTO, 1983, 1985). Regarding the intrinsic relationship between diagnosis and treatment, the impossibility of these children immediately allowing speech and the presence of others into their “play” was discussed. With treatment, however, turning points in the children's relationship with language could be noticed. Clinical actions, in fact, can leverage significant shifts “in the body of speech/writing” and in the child's position in relation to the other, shifts that were not determined by changes in behavior, but by transformations in the child's listening to the other's speech. and for speech itself. To do this, the clinician starts by listening and accepting the (invernacular) material of their speeches/gestures